New developments in the management of psoriasis and psoriatic arthritis: a focus on apremilast - Palfreeman AC; McNamee KE; McCann FE (Dove Medical Press, 2013)
Andrew C Palfreeman, Kay E McNamee, Fiona E McCann The Kennedy Institute of Rheumatology, Nuffield Department of Orthopedics, Rheumatology and Musculoskeletal Sciences, University of Oxford, London, UK Abstract: Psoriasis is a chronic inflammatory skin disease, most commonly resulting in the occurrence of red and silver scaly plaques. About 30% of psoriasis sufferers develop psoriatic arthritis (PsA), a disorder that presents with additional joint inflammation and other clinical features. At present, the most effective treatment for moderate and severe psoriasis and PsA are biologics such as antitumor necrosis factor alpha therapy. Biologics are costly and typically require repeated injections; hence, the development of novel, orally available, small molecular inhibitors that are less expensive to produce is highly desirable. The phosphodiesterase 4 inhibitor apremilast is a small molecular inhibitor that acts by increasing cyclic adenosine monophosphate levels, ultimately suppressing tumor necrosis alpha production. Apremilast has been tested in a number of psoriasis and PsA pilot and Phase II trials to evaluate its efficacy and safety. More recently, three larger double-blinded, and randomized multicenter studies demonstrate that apremilast is efficacious in the treatment of psoriasis and PsA, with significantly higher numbers of apremilast-treated patients achieving endpoints of a 75% reduction compared to baseline in Psoriasis Area and Severity Index (PASI-75) or American College of Rheumatology-20 scores, relative to placebo. This encouraging data, along with a tolerable incidence of mild to moderate adverse events, has led to the initiation of several large Phase III trials that aim to further validate apremilast as a treatment for psoriasis and PsA. Here, we provide an overview of the current treatments for psoriasis and PsA, and summarize the findings from multiple Phase II clinical trials where the effects of apremilast in the treatment of psoriasis and PsA patients have been investigated. Keywords: apremilast, psoriasis, psoriatic arthritis, phosphodiesterase inhibitor